Development of a non-derivatized LC-MS/MS method for simultaneous quantification of ten neurotransmitters in five neuroinflammatory mouse models - Bao Sun; Zhaodi Xia; Chen Wang; Mengyao Wu; Ru Tie; Yilin Ru; Yaxi Meng; Lu Bai; Ying Zhang; Pu Jia; Shixiang Wang; Bing Qi; et al. (Talanta Open)
Sensitive and comprehensive measurement of systemic metabolites of Trp, Phe and Glu in biological samples is effective for understanding the pathogenesis of pain, anxiety, depression, PTSD and other neurological diseases. This study developed a LC-MS/MS method for simultaneous monitoring the 10 neurotransmitters in mouse hippocampus, and applied it to investigate their changes in five neuroinflammatory mouse models. The quantitative analysis of 10 neurotransmitters, including Gamma-aminobutyric acid (γ-GABA), l-Glutamate (Glu), l-Glutamine (Gln), l-Tryptophan (Trp), Serotonin (5-HT), 5-Hydroxyindoleacetic acid (5-HIAA), l-Phenylalanine (Phe), l-Tyrosine (L-Tyr), Dopamine (DA), Levodopa (L-DOPA) was achieved within a chromatographic separation time of 4.5 min by the application of ThermoFisher Scientific™ Vanquish™ HPLC coupled to ThermoFisher ScientificTM TSQ QuantisTM mass spectrometer. Optimized chromatographic separation as well as high sensitivity allow the simultaneous analysis and precise quantification of ten neurotransmitters in mouse hippocampus. The limits of detection in sample ranged from 0.3pg (Phe) to 0.1 μg (γ-GABA). Recoveries were between 88.0 to 113.8 %, the mean intra - day and inter - day coefficient of variation of 5.56 % and 4.72 %, respectively. The matrix effect was from 85.1 to 114.9 %. A series of significant changes in five neuroinflammatory mouse models can be detected. γ-GABA, Glu, Gln, DA, Phe, l-Tyr, 5-HIAA were decreased in depression model. Gln and Glu were decreased in PTSD model. 5-HIAA was elevated in anxiety. 5-HIAA and l-Trp were decreased in CFA and SNI model, respectively. In conclusion, a LC-MS/MS method for simultaneous measurement of 10 neurotransmitters in mouse hippocampus was developed and successfully applied to investigation of the changes in five neuroinflammatory mouse models. The method would be expected to provide applicability to the study of the mechanisms of neurological diseases associated with these neurotransmitters.